The Implementation of the Merdeka Curriculum in Islamic Education Learning at Senior High School - Najamuddin, Andi; Mansur, Mansur; Alias, Alias (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study examines the implementation of the Merdeka Curriculum in Islamic Education learning at SMAN 1 Nunukan Selatan, Nunukan District, North Kalimantan Province. The objectives of the research are: 1) to understand how Islamic Education teachers implement the Merdeka Curriculum at SMAN 1 Nunukan Selatan, 2) to identify the challenges faced by teachers in implementing Islamic Education through the Merdeka Curriculum, and 3) to explore the solutions provided by teachers in overcoming these challenges. This research adopts a descriptive qualitative approach with the research location at SMAN 1 Nunukan Selatan, Nunukan District. Data collection was carried out through observation, interviews, and documentation, with respondents including the school principal, curriculum supervisor, Islamic Education teachers, and students. Research instruments used include the researcher, observation guidelines, interview guidelines, and documentation. Data were analyzed using steps such as data collection, data reduction, data presentation, and concluded with data verification. The results show that the implementation of Islamic Education learning at SMAN 1 Nunukan Selatan has not yet been optimal in applying the Merdeka Curriculum. This is evident from the teachers' readiness, as they feel that the curriculum still requires adjustments and processes. The teaching methods continue to follow the previous curriculum patterns, and there are difficulties in preparing teaching materials. Additionally, limitations in the availability and utilization of facilities and infrastructure also pose challenges. However, Islamic Education teachers strive to optimize learning by adapting quickly, developing competencies, enhancing creativity, and utilizing technology for more effective teaching. Collaboration with colleagues and support from various parties are crucial solutions for teachers in implementing Islamic Education through the Merdeka Curriculum.